Comparative Insight into the Performance of Two Different Amine‐Functionalized CNTs for the Chemical Speciation of Chromium. Issue 21 (4th June 2020) - Sharma, Niharika; Tiwari, Shelja; Saxena, Reena
Abstract: Persistent industrial activities have led to an increase in the chromium content in environmental water bodies. The accurate quantification of trace chromium species such as Cr(III) and Cr(VI) is crucial as Cr(VI) can exhibit toxicity even at sub‐ppb levels. We report herein a comparative chromium speciation study using two chemically functionalized nanoadsorbents and determination with hyphenated flow injection‐flame atomic absorption spectrometry (FI‐FAAS). The most efficient preconcentration performance was obtained by optimizing the chemical and hydrodynamic parameters. Cr(VI) concentration was ascertained by the reduction to Cr(III) as the nanoadsorbents were selective for Cr(III) adsorption only; thus, speciation was achieved. The method was selective for Cr(III) in the presence of interfering matrix components. Preconcentration factor >90 and detection limit <0.11 μg L −1 were obtained for both the nanoadsorbents (%RSD∼1.0 %). The adsorption capacity of CNT‐TYR and CNT‐ASA was found to be 42.0 and 43.2 mg g −1, respectively. The application of the proposed method to contaminated water samples gave recoveries >95 %. The accuracy of the method was verified using NIST SRM 1640a. Abstract : This paper reports the performance comparison of two different amine functionalized nanoadsorbents for the preconcentrative speciation of chromium in a hyphenated FI‐FAAS system. The prepared nanoadsorbents could selectively preconcentrate Cr(III) in the presence of Cr(VI) and other matrix components, thus leading to the speciation of Cr(III) from Cr(VI). The hyphenated system was applied to industrially contaminated water samples and >95 % recovery was achieved. The reported method is fast, selective, and highly reliable for chromium speciation in complex aqueous matrices.